The Digital Classroom: Systematic Review of Use of English as a Foreign Language (EFL) in Teaching in Collaborative Online Settings - Yingxin, Xu; Singh, Charanjit Kaur Swaran; Bailey, Richard Peter; Arivayagan, Keetanjaly (2024)
This study systematically reviews existing literature on the use of collaborative online settings for teaching English as a foreign language (EFL). Covering 37 peer-reviewed articles published between 2013 and 2024, the review examines various aspects of online collaborative EFL teaching, including the digital platforms utilized, the educational environments, and the specific language skills targeted. The findings indicate that collaborative online environments can enhance EFL learners' language proficiency through interactive learning, feedback techniques, and personalized learning. Additionally, the review found that such environments primarily improve learners' writing skills, with oral and speaking skills also benefiting. However, challenges such as learner distraction, Internet connectivity issues, lack of resources, and limited technical skills were identified as barriers to adopting collaborative online settings in EFL teaching. Strategies to mitigate these challenges such as the use self-created video materials, training, access to the Internet, among others, were discussed. The implications of these findings suggest that educators should incorporate digital collaborative tools to enhance learning outcomes, policymakers should support technological integration in language education, and researchers should address the identified gaps to develop more effective teaching strategies and educational policies.